The deception provisions of sections 10(12) and 10(13) of the Trade Marks Act, 194 of 1993 - Papadopoulos, Sylvia (University of Pretoria, 2023)
Mini Dissertation (LLM (Intellectual Property Law))--University of Pretoria, 2022.